Protecting healthcare workers against SARS-CoV-2 - Ferrinho, Paulo (2020)
COVID-19 is a serious threat to the responsiveness of health services. In this context, health workers (HW) are expected to work long hours, under great professional, family and emotional pressure, with resources often inadequate, while accepting the dangers inherent in the activity, the proximity to infectious people, inseparable dangers of work environments. The impact of the pandemic is reflected in HW as individuals, but it also affects their families, both in terms of less time available and in terms of mental health. Factors such as quantity, cost, availability as well as the lack of habit of use of personal protective equipment (PPE) affects its use by HW. The use of PPE is not sufficient protection if not accompanied by the adoption of other infection control measures, such as hand hygiene and physical distance. Priority should also be given to testing HW. The pandemic challenges health systems to a dynamic adaptation in the management of existing resources, with a special focus on information systems. Telemedicine services can potentially reduce direct contact with the patients and, therefore, the risk of SARS-CoV-2 infection. In the perspective of a SARS-CoV-2 vaccine soon, HW should be among the priority groups to receive it. HW are one of the most important resources in a country, so it is necessary to take care of these professionals in all aspects in health organizations, so that HW are able to respond to the demands of this pandemic and others that will eventually occur in the future. The pandemic does not recognize borders. It must be addressed in a way that strengthens international collaboration that enables solidarity and equitable resource sharing.